Density driven damage mechanics (D3-M) model for concrete II: fully coupled chemo-mechanical damage. Issue 4 (21st March 2022) - Murru, Pavitra T.; Grasley, Zachary; Torrence, Christa; Rajagopal, K.R.; Garboczi, Edward
ABSTRACT: In Part I, a density driven damage mechanics (D3-M) approach and its application to model mechanical damage in concrete are presented. In this study, chemical and chemo-mechanical damage in concrete were modelled using the D3-M approach. It is proposed that reductions in local density in certain regions, created when concrete is subjected to chemical attack or coupled chemical-mechanical loading, result in reduced stiffness and strength of the material. The D3-M modelling approach stands out among the past efforts to predict the response of concrete to mechanical and chemical stimuli due to its ability to effectively model the mechanical, chemical, and coupled mechanical-chemical responses of concrete using a consistent framework and a single constitutive equation for both types of damage. Model simulations indicate that the response of the material to a scenario where chemical and mechanical loads are acting simultaneously cannot be considered equivalent to the response obtained by superposing the separate responses to independent mechanical and chemical loads.